Flexible versus structured support for reasoning: enhancing analytical reasoning through a flexible analytic technique. Issue 2 (23rd February 2021) - Stromer-Galley, Jennifer; Rossini, Patricia; Kenski, Kate; McKernan, Brian; Clegg, Benjamin; Folkestad, James; Østerlund, Carsten; Schooler, Lael; Boichak, Olga; Canzonetta, Jordan; Martey, Rosa Mikeal; Pavlich, Corey; et al.
ABSTRACT: Structured analytic techniques (SATs) help the intelligence community reduce flaws in cognition that lead to faulty reasoning. To ascertain whether SATs provide benefits to reasoning we conducted an experiment within a web-based application, comparing three conditions: 1) unaided reasoning, 2) a prototypical order-based SAT and 3) a flexible, process-based SAT that we call TRACE. Our findings suggest that the more flexible SAT generated higher quality reasoning compared to the other conditions. Consequently, techniques and training that support flexible analytical processes rather than those that require a set sequence of steps may be more beneficial to intelligence analysis and complex reasoning.  Keywords: structured analytical techniques, Analysis of Competing Hypotheses, tradecraft, cognitive biases, experiments.